Patriarchy Culture in Gender Equality Concept: Islamic Perspective - Tri Winda Oktavia; Firyal Iftikhar Cikalkinanty; Agus Fakhruddin (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The condition of a patriarchal culture that is rooted in society causes many cases of gender inequality in which women are the main victims. This is because the perception of gender of men and women has different characteristics, so it can be said that men are more dominant than women. In addition, Islamic religious perspective on this phenomenon, where there are often misconceptions about the understanding of Islamic religious knowledge, is reason for the emergence of a patriarchal culture that continues to take root in society. This study has the purpose to find out descriptively and meaningfully of patriarchal culture in concept of gender equality. In this study uses qualitative research methods through a literature study of relevant books, literature, and journals. As a result that patriarchal culture manifests gender inequality. Not only in a family environment but also in an educational environment, work environment, etc. Domestic violence experienced by women is a form of gender inequality. While other forms are marginalization, subordination, stereotypes, and dual roles. In addition, Islamic teachings originating from explanations in the Qur'an have emphasized that men and women have equal rights in terms of worship (spiritual) and social activities. However, a lack of public understanding has made patriarchal culture take root to this day.